Genome-wide identification, phylogeny and expression analysis of the bZIP gene family in Alfalfa (Medicago sativa). Issue 1 (1st January 2021) - Liu, Shu-Xia; Qin, Bin; Fang, Qing-xi; Zhang, Wen-Jing; Zhang, Zhe-Yu; Liu, Yang-Cheng; Li, Wei-Jia; Du, Chao; Liu, Xian-xian; Zhang, You-li; Guo, Yong-Xia
Abstract: Among eukaryotic transcription factors, the basic leucine zipper (bZIP) transcription factor is the most widely distributed and the most conserved protein. Alfalfa ( Medicago sativa ) is the largest forage crop in the world. However, few studies have evaluated the bZIP family in Alfalfa. In this study, bZIP genes in Alfalfa were identified, with 57 MsbZIPs being distributed into 11 sub-families in the phylogenetic tree. Motif and gene structure analysis revealed that the eleven subfamilies had similar motifs and gene structures, 15 cis -acting elements in MsbZIPs, including eight elements in hormones and four in plant stress resistance; 57 MsbZIPs were localized on 8 chromosomes, among which chr3 and chr4 had more collinearities, and MsbZIPs had more collinearity with the soybean. Tissue specific expression revealed that MsbZIPs were highly expressed in leaves and roots. These findings formed a foundation for further studies on functional characteristics, evolution and biological functions of bZIP transcription factors in alfalfa.